2015
DOI: 10.1155/2015/750846
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sulfurization Pressure on the Conversion Efficiency of Cosputtered Cu2ZnSnS4Thin Film Solar Cells

Abstract: We report herein Cu 2 ZnSnS 4 (CZTS) thin film solar cells with 6.75% conversion efficiency, without an antireflection coating. The CZTS precursors have been prepared by cosputtering using three different targets on Mo-coated substrates: copper (Cu), tin sulfide (SnS), and zinc (Zn). The postsulfurization was carried out at different pressures in a H 2 S/N 2 environment at 550 ∘ C for one hour. A comparative study on the performances of solar cells with CZTS absorber layers prepared at different sulfurization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…These images show that some of the CZTS layers, used for device fabrications, include void formations. In the CZTS literature, it is often reported that the voids at the Mo-CZTS interface, which are called Kirkendall voids, form due to the different interdiffusion velocities of Cu, Zn, and Sn elements [58,59]. From the SEM cross sections of devices shown in figure 11, the thicknesses of CdS buffer layers deposited for 90, 75, 60 and 45 min were measured as 140.0, 134.9, 102.5, and 75.5 nm for cells 1 to 4, respectively.…”
Section: Device Characterizationsmentioning
confidence: 99%
“…These images show that some of the CZTS layers, used for device fabrications, include void formations. In the CZTS literature, it is often reported that the voids at the Mo-CZTS interface, which are called Kirkendall voids, form due to the different interdiffusion velocities of Cu, Zn, and Sn elements [58,59]. From the SEM cross sections of devices shown in figure 11, the thicknesses of CdS buffer layers deposited for 90, 75, 60 and 45 min were measured as 140.0, 134.9, 102.5, and 75.5 nm for cells 1 to 4, respectively.…”
Section: Device Characterizationsmentioning
confidence: 99%